Recombination Between Endogenous and Exogenous Simian Virus 40 Genes. I. Rescue of a Simian Virus 40 Temperature-Sensitive Mutant by Passage in Permissive Transformed Monkey Lines - Gluzman, Y. (1977)
Passage of the simian virus 40 (SV40) temperature-sensitive (ts) mutant tsD202 at the permissive temperature in each of three permissive lines of SV40-transformed monkey CV1 cells resulted in the emergence of temperature-insensitive virus, which plated like wild-type SV40 at the restrictive temperature on normal CV1 cells. In independent experiments, the amount of temperature-insensitive virus that appeared after passage on transformed cells was from 10(3)- to 10(6)-fold greater than the amount of ts-revertant virus that appeared after an equal number of passages in nontransformed CV1 cells. The virus rescued by passage on transformed cells bred true upon sequential plaque purification, plated on normal CV1 cells with single-hit kinetics at the restrictive temperature, and displayed no selective growth advantage on transformed cells compared to non-transformed cells. Hence, the reversion of the ts phenotype is neither due to complementation effects nor to the selection of preexisting revertants, which grow better on transformed cells. In the accompanying article (T. Vogel et al., J. Virol. 24:541-550, 1977), we present biochemical evidence that the rescue of tsD202 mediated by passage on transformed cells is due to recombination with the resident SV40 genome. Parallel experiments in which tsA, tsB, and tsC SV40 mutants were passaged in each of the three permissive lines of SV40-transformed monkey cells resulted in either only borderline levels of rescue (tsA mutants) or no detectable rescue (tsB and tsC mutants). Evidence is presented that the resident SV40 genome of the transformed monkey lines is itself a late ts mutant, and we suggest that this accounts for the lack of detectable rescue of the tsB and tsC mutants. We furthermore suggest that the borderline level of rescue observed with two tsA mutants is related to a previous finding (Y. Gluzman et al., J. Virol. 22:256-266, 1977) which indicated that the resident SV40 genome of the permissive transformed monkey cells is defective in the function required for initiation of viral DNA synthesis.